Targeted next-generation sequencing for the molecular diagnosis of hereditary angioedema due to C1-inhibitor deficiency - Loules, Gedeon; Zamanakou, Maria; Parsopoulou, Faidra; Vatsiou, Sofia; Psarros, Fotis; Csuka, Dorottya; Porebski, Grzegorz; Obtulowicz, Krystyna; Valerieva, Anna; Staevska, Maria; López-Lera, Alberto; López-Trascasa, Margarita; et al. (Gene, 2018)
SERPING1 genotyping of subjects suspicious for hereditary angioedema due to C1-INH deficiency (C1-INH-HAE) is important for clinical practice as well as for research reasons. Conventional approaches towards the detection of C1-INH-HAE-associated SERPING1 variants are cumbersome and time-demanding with many pitfalls. To take advantage of the benefits of next-generation sequencing (NGS) technology, we developed and validated a custom NGS platform that, by targeting the entire SERPING1 gene, facilitates genetic testing of C1-INH-HAE patients in clinical practice. In total, 135 different C1-INH-HAE-associated SERPING1 variants, out of the approximately 450 reported, along with 115 negative controls and 95 randomly selected DNA samples from affected family members of C1-INH-HAE index patients, were included in the forward and reverse validation processes of this platform. Our platform's performance, i.e. analytical sensitivity of 98.96%, a false negative rate of 1.05%, analytical specificity 100%, a false positive rate equal to zero, accuracy of 99.35%, and repeatability of 100% recommends its implementation as a first line approach for the genetic testing of C1-INH-HAE patients or as a confirmatory method. A noteworthy advantage of our platform is the concomitant detection of single nucleotide variants and copy number variations throughout the whole length of the SERPING1 gene, moreover providing information about the size and the localization of the latter. During our study, 15 novel C1-INH-HAE-related SERPING1 variants were detected. •A validated next-generation sequencing platform targeting the entire SERPING1 gene is presented.•This platform is proposed for the first-line or confirmatory genotyping of C1-INH-HAE patients.•Beyond SNVs, CNVs along with their size and localization can be detected throughout the whole length of SERPING1 gene.•Fifteen novel, C1-INH-HAE-associated mutations are reported.